Better healthcare setting for better healthcare service quality: An empirical analysis of Indian consumers' perspective. Issue 10 (8th July 2019) - Kondasani, Rama Koteswara Rao; Panda, Rajeev Kumar; Basu, R.
Abstract : Purpose: The purpose of this paper is to assess and compare different private healthcare settings based on perceived service quality in Indian context using analytical hierarchy process (AHP). The Indian private healthcare sector has been controlled by three categories of healthcare settings, namely, nursing clinics (NCs), non-corporate hospitals (NCHs) and corporate hospitals (CHs). Design/methodology/approach: AHP was used to rank order of healthcare setting regarding the service quality dimensions and relative standings of every service provider with respect to its competitors. The authors collected random data from nine private hospitals situated in eastern and southern India. The authors proposed a feasible appraising approach based on AHP to decide the sustainability priority of dimensions like reliability, physical environment, empathy, efficiency, timeliness, transparency, affordability, communication, appropriateness and consistency in the Indian private healthcare industry. Findings: The result demonstrates that Indian NCHs are performing better on customers' perceived service quality, followed by CHs and NCs. The comparative performance of healthcare settings is an attempt to establish a performance ranking. Originality/value: This research assesses dimensions of the service quality that need urgent attention. The results may provide insight to healthcare managers as to how they can improve their service quality in order to match customer expectation and to improve business performance.